Hubungan Antara Loneliness Dengan Fear Of MissingOut Pada Remaja Yang Menggunakan Instagram Di SMA Pertiwi 1 Kota Padang - Fenia, Selvi Zola; Nastasia , Krisnova (CV. ITTC INDONESIA, 2021)
The purpose of this study was to determine whether there is an influence between loneliness (loneliness) and fear of missing out among teenage students who use Instagram at SMA Pertiwi 1 Kota Padang. The variables in this study consisted of two variables, namely the loneliness tool and the fear of missing out. The research method used in this research is quantitative research methods. The measuring instrument used is a Likert scale questionnaire based on the loneliness scale and the fear of missing out scale. The sampling technique used is random sampling, with a total of 90 people, namely teenage students who use Instagram in high school. Pertiwi 1 Padang City The results of the study found that 16% of the loneliess level was low and 70% was moderate, meanwhile 17% of the teenage students had a high level ofloneliness.